Ratna Sagar Private Limited - Dixit, Mukund R.; Anil Kumar, H. ([London] : SAGE, 2016)
The case presents the efforts of Dr Dhanesh Jain, founder of Ratna Sagar Publications, to innovate in children's publishing space. His innovations received mixed response. Commercial success was delayed. Adoption of innovations by the educational institutions did not happen as expected but the innovations, however, created opportunities for other business ventures. Dr Jain is wondering whether the innovation efforts were worth their while.
Originally Published in: Dixit, M. R., & Kumar, H. A. (2015). Ratna Sagar Private Limited. BP0383. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Jain, Dhanesh; Ratna Sagar (Firm); Creative ability in business -- Case studies; Technological innovations -- Case studies; Publishers and publishing -- India -- Case studies; Strategic planning -- Case studies; Competition -- Case studies